Factor Analysis of the Incident of Chills in Sectio Caesarea Patients with Spinal Anesthesia in Hospital - Islaeli, Islaeli; Wahyuni, Sri; Arief, Khumaidi; Laisouw, Meilany; Malawat, Ratna; Megasari, Anis Laela (International Journal of Health Sciences, 2024)
Spinal anesthesia is a regional anesthetic technique that is produced by blocking the spinal nerves in the subarachnoid space with local anesthetic substances. The spinal anesthesia technique is widely used because it is a simple, effective technique, relatively safe for the nervous system, a strong level of analgesia, the patient remains conscious, sufficient muscle relaxation, less surgical wound bleeding, less risk of aspiration, and faster recovery of digestive tract function. In the intra- or post-operative stage, patients with spinal anesthesia often complain of nausea, vomiting, a feeling of heaviness in both lower extremities, and shivering which occurs due to the secondary effects of spinal analgesic drugs which produce sympathetic block, muscle relaxation, and sensory block of peripheral temperature receptors, thereby inhibiting the response. temperature compensation. The aim of this study was to determine the factors that cause shivering in intra spinal anesthesia patients at Aliya Kendari Sj Hospital. This research method is an analytical observational study with a cross sectional approach using a random sampling technique to obtain the number of caesarean section patients. The analysis used is Logistic Regression. The research results showed a significant relationship between operation time, operating room temperature, LILA. The conclusion is that the most dominant factor influencing the incidence of shivering is body temperature.